Regulatory Mechanisms of Muscle Mass: The Critical Role of Resistance Training in Children and Adolescent - Valero-Breton, M; Cabello-Verrugio, C (Springer, 2023)
Muscle mass and strength are subjected to several regulations. We found endocrine signals such as growth hormone, insulin-like growth factor 1, testosterone, thyroid hormones, and glucocorticoids among them. Neural inputs also influence muscle development, modulating mass and strength. Among the external stimuli that modulate these muscular features is physical training such as resistance and endurance training. Specifically, resistance training can mediate an increase in muscle mass by hypertrophy in adults, but the effects in children and adolescents are full of myths for most of the population. However, the evidence shows that the impact of resistance training on children and adolescents is clear and provides a wide range of benefits. However, qualified professionals must be available since exercise prescription and subsequent supervision must follow this population’s abilities, needs, and interests. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.